The Value of the Voting Right: A Study of the Milan Stock Exchange Experience - Zingales, Luigi (Review of Financial Studies, 1994)
I study the large premium (82 percent) attributed to voting shares on the Milan Stock Exchange. The premium varies according to the ownership structure and the concentration of the voting rights, and it can be rationalized in the presence of enormous private benefits of control. A case study seems to indicate that in Italy private benefits of control can easily be worth more than 60 percent of the value of nonvoting equity. A tentative explanation for these findings is provided. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.